4CPS-007 Cost minimisation study: switch vial to pen in geriatrics. (March 2019) - Castanié, I; Vert, C; Puyo, P; Mange, AS; Pages, A; Mccambridge, C; Cestac, P
Abstract : Background: Insulin glargine (IG; original drug and biosimilar) is on the market in vial or pen presentations with different costs. The biosimilar drug is less expensive than the original drug. Purpose: The main objective was to evaluate the incremental cost of changing IG vial by (original and biosimilar IG) pen over a 1 year period and the nurses' implementation and acceptability in geriatric wards. Material and methods: IG prescription (number of UI per patient and IG vial consumption) and costs were retrospectively collected over a 1 year period (August 2017 to August 2018). Nurses answered a survey in each geriatric ward to make an inventory of practices and to assess the acceptability of replacing vials with pens. The comparison of security and ease of use of vial and pen (0 to 10 score, 0 bad possibility and 10 best possibility) were performed using the Wilcoxon signed-rank test. Results: Three-hundred and fifty-three patients were included, and the total cost for 108 vials of IG vials was €2700, equivalent to 408 pens of IG for €775.2. The use of vials represents a cost of €7.65 per patient, whereas the use of pens represents a cost of €2.19 per patient. Prescribing biosimilars could be a strategic approach to minimise pharmaceutical costs: in our study the use of 408 IG biosimilar pens would represents a cost per patient of €0.17. In 18 responses to the survey, six nurses did not want to use the pens for various reasons: 'too many pens in the ward', 'waste', 'no visibility on the quantity injected'. The pens have a best security assessment (mean score difference=1.94, p=0.014) and ease-of-use assessment (mean score difference=3.05, p=0.007) rather than vials. Fifty-five per cent of nurses think, mistakenly, that the pen is more expensive than the vial. Conclusion: This study showed that using IG pens rather than vials and biosimilar prescription would be cost saving. This result shows that nurses are ready to accept replacing vials with pens. References and/or acknowledgements: No conflict of interest.